College Students’ Level of Mathematics Anxiety and Academic Performance:A Basis for a Proposed Intervention Program - Viray-Ariola, Cherry Amor (Future Science / FSH-PH Publications, 2025)
Mathematics anxiety is a concern in higher education, often linked to students’ academics and emotional well-being. This study examined the mathematics anxiety level and academic performance of students enrolled in GEC 002-Mathematics in the Modern World, a general education course at the University of La Salette. It specifically explored students’ demographic profile, academic performance, and mathematics anxiety level across the following factors: physical and emotional, assessment, and social. Differences or relationships between their anxiety levels and their profile or performance were also tested. This descriptive-correlational study involved 265 students from five departments, selected through stratified sampling. Data gathered through a questionnaire on mathematics anxiety and students’ grades in GEC 002 were analyzed using frequency and percentage, weighted mean, independent samples t-test, one-way ANOVA, and Pearson correlation. Most students performed well academically, with moderate overall anxiety. Assessment-related factors ranked highest, followed by social factors, while physical and emotional symptoms were less evident. No significant differences in mathematics anxiety were found across age, gender, or department. However, students with “excellent” academic performance reported significantly lower anxiety (p = 0.003). A weak, statistically significant positive correlation emerged between mathematics anxiety and academic performance, suggesting that, in this context, anxiety may function as a slight motivator rather than a debilitating hindrance, implying other factors play a considerable role. An intervention program was proposed to promote academic success and emotional well-being. Although limited to a single institution and based on self-reported, cross-sectional data, the study highlights the importance of addressing mathematics anxiety in HEIs.